Structure and Vibrational Properties of Potassium-Promoted Tungsten Oxide Catalyst Monomeric Sites Supported on Alumina (K2O/WO3/Al2O3) Characterized Using Periodic Density Functional Theory - Kiani, Daniyal (2018)
Al2O3-supported tungsten oxide catalysts have been instrumental in many industrially relevant reactions and their reactivity is controlled by their molecular structure. In turn, their molecular structure has primarily been derived via Raman measurements with assignments made using model compounds of known local (molecular) coordination. In this work, the structure and simulated Raman spectra of unpromoted and K+-promoted tungsten oxide catalyst monomeric sites supported on γ-Al2O3(110) (K2O/WOx/γ-Al2O3(110)) were studied using periodic DFT methods. Two different WOx-grafted monomers on the γ-Al2O3(110) surface were identified with a total energy difference of 0.17 eV between both structures. Importantly, both structures showed the presence of W=O and W-OH moieties, thus providing additional insights into experimental Raman data, which typically describe only W=O moieties. The grafted WO3 species were stabilized when the present W-OH groups were oriented toward the alumina surface leading to the formation of H-bonds, calculated at 1039 cm-1, for example in the vicinity of the W=O vibrations. The W=O bond length was altered in the presence of K+, as shown experimentally and theoretically in blue shifting of the Raman band corresponding to W=O. The W vibrations were well localized in the calculated spectra, and little shifts were observed upon the different WOx molecular geometry, explaining why a single Raman peak is mostly observed experimentally. The acidity of the lowest energy catalyst structures was investigated by simulated NH3 adsorption vibrational frequency and binding energy calculations. Results suggested that NH3 prefers to bind in a Lewis-like structure with no proton donation from either W-OH or Al-OH moiety. This challenged some of the literature observations where Brønsted acid sites have been suggested to exist on near-monolayer coverage WOx species on γ-Al2O3 prepared by calcining at moderate (400 °C) to high temperatures (700 °C). Overall, this work provided new insights into the molecular structure of WOx/γ-Al2O3 and K2O/WOx/γ-Al2O3 catalysts not immediately available from experimental measurements alone.